1988
DOI: 10.1111/j.1600-0765.1988.tb01371.x
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural evidence of directed cell migration during initial cementoblast differentiation in root formation

Abstract: Root formation in 14‐day‐old Sprague‐Dawley rats was studied by light and electron microscopy. Special attention was focused on initial cementoblast differentiation. Disruption of the epithelial root sheath appears to be a consequence of directed cell migration by cells of the dental follicle proper which undergo differentiation into precementoblasts. Precementoblasts rapidly develop polarity towards the dentin, exhibiting major cytoplasmic processes rich in cytoplasmic filaments. These processes grow toward a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
56
0
3

Year Published

1996
1996
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(63 citation statements)
references
References 27 publications
4
56
0
3
Order By: Relevance
“…These proteins may mediate root and/or cementum formation, and do not appear to become major constituents of cementum (Luan et al, 2006). We think it likely that major interfibrillar matrices such as bone sialoprotein and osteopontin are products of dental follicle-derived cementoblasts in normal cementogenesis (Yamamoto, 1986;Cho and Garant, 1988Diekwisch, 2001;Yamamoto and Wakita, 1990;Yamamoto et al, 2004Yamamoto et al, , 2007Hirata and …”
Section: Runx2-keratin Double Stainingmentioning
confidence: 99%
“…These proteins may mediate root and/or cementum formation, and do not appear to become major constituents of cementum (Luan et al, 2006). We think it likely that major interfibrillar matrices such as bone sialoprotein and osteopontin are products of dental follicle-derived cementoblasts in normal cementogenesis (Yamamoto, 1986;Cho and Garant, 1988Diekwisch, 2001;Yamamoto and Wakita, 1990;Yamamoto et al, 2004Yamamoto et al, , 2007Hirata and …”
Section: Runx2-keratin Double Stainingmentioning
confidence: 99%
“…These findings suggest that the epithelial sheath secretes these enzymes to disintegrate itself. Cho and Garant (1988) present transmission electron micrographs in which dental follicle cells appeared to invade the epithelial sheath with their cytoplasmic projections, suggesting that dental follicle cells force their projections into the epithelial sheath to disintegrate it. An electron microscopy study by Suzuki et al (2002) also suggests that invasion of dental follicle cells causes epithelial sheath fragmentation.…”
Section: Fragmentation Of Hertwig's Epithelial Root Sheathmentioning
confidence: 99%
“…Two mechanisms have been proposed for the degradation. First, external mechanical damage or invasion of dental follicle cells into the epithelial sheath causes degradation (Cho and Garant 1988;Suzuki et al 2002). Alternatively, epithelial sheath cells secrete matrix-degrading enzymes that disintegrate the factors (Hirata and Nakamura 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The attachment of periodontal ligament cells to CAP appears to be mediated by ␣5␤1 integrin (Ivanovski et al, 1999); however, it has not been demonstrated that HERS cells in vivo express this protein. Based on transplantation and autoradiographic experiments, it has been suggested that cells from the dental follicle are the precursors of cementoblast cells (Yoshikawa and Kollar, 1981;Palmer and Lumsden, 1987;Osborn and Price, 1988;Cho and Garant, 1988;Diekwisch, 2001). Recent experiments by Chai et al (2000) indicate a common neural crest origin for dental follicle and cementoblast cells.…”
Section: Role and Fate Of Hers?mentioning
confidence: 99%